Spin-sate reconfiguration induced by alternating magnetic field for efficient oxygen evolution reaction - Zhou, Gang; Wang, Peifang; Li, Hao; Hu, Bin; Sun, Yan; Huang, Rong; Liu, Lizhe (Nature communications, 2021)
Oxygen evolution reaction (OER) plays a determining role in electrochemical energy conversion devices, but challenges remain due to the lack of effective low-cost electrocatalysts and insufficient understanding about sluggish reaction kinetics. Distinguish from complex nano-structuring, this work focuses on the spin-related charge transfer and orbital interaction between catalysts and intermediates to accelerate catalytic reaction kinetics. Herein, we propose a simple magnetic-stimulation approach to rearrange spin electron occupation in noble-metal-free metal-organic frameworks (MOFs) with a feature of thermal-differentiated superlattice, in which the localized magnetic heating in periodic spatial distribution makes the spin flip occur at particular active sites, demonstrating a spin-dependent reaction pathway. As a result, the spin-rearranged Co Mn MOF displays mass activities of 3514.7 A g with an overpotential of ~0.27 V, which is 21.1 times that of pristine MOF. Our findings provide a new paradigm for designing spin electrocatalysis and steering reaction kinetics.